Syntaxonomy of heliophylous ephemeroids and winter ephemera plant groups of seasonal (early spring) vegetation on the Dnipro Forest-Steppe (Ukraine). (CHORNOMORSKI BOTANICAL JOURNAL, 2018)
During seasonal explorations (early spring) of the Dnipro Forest-Steppe vegetation in the outskirs of Kaniv city plant communities (34 releves) which names are absent in the list of syntaxa of Ukrainian vegetation have been identified. They are mostly secondary or semi-natural plant groups of spring perennials, ephemera and ephemeroids with winter type germination on light condensed substrates, drying out in summer. The upper stratums of the soil profile are characterized by the rapid mineralization of organic matter after the winter period with wet soil. These phytocoenoses are most often found as the spots, streaks along paths and roads, on antropogenic elements of relief. According to the presence of common diagnostic species – Medicago lupulina, Erodium cicutarium, Plantago lanceolata, Poa bulbosa, Lolium perenne, the investigated plant groups should belong to the class Poetea bulbosae which nominally is given in “The Review of Ukrainian vegetation”. Diagnostic value is increased due to growth in investigated groups as well Buglossoides czernjajevii, Valerianella locusta, Lamium amplexicaule, Arabidopsis thaliana, Veronica hederifolia, V. persica, V. verna, Erophila verna, Anisantha tectorum, Draba nemorosa, Ranunculus illyricus etc. Most of these species in Ukrainian flora are indicated as diagnostic for classes: Koelerio-Corynephoretea canescentis, Sedo-Scleranthetea, Festuco-Brometea. Such interpretation is a consequence of their frequent presence in this type phytocoenoses but does not correspond to the biomorpho-phenotypic type status of the main aedificators of these classes groups. The main elements for Koelerio-Corynephoretea canescentis are euxerophilous cereals summer-vegetation hemicryptophytes, for Sedo-Scleranthetea – summer-vegetation succulent hamephytes and hemicryptophytes, for Festuco-Brometea – summer-vegetation megatrophic xerophytes with wide biomorphological spectrum. As for the discussed group of plants, it should be noted that they occur in groups of these classes and can form small area phytocoenoses with predominance and determining influence. Identification of these plant groups with the participation of heliophilic ephemeroids and winter ephemera promotes to describe the new association Anisantho tectorii-Poetum bulbosae ass. nova with three sub-associations (plantaginetosum, buglossoidetosum, typicum) included to the new alliance Anisantho tectorii-Poeion bulbosae all. nova from the order Poetalia bulbosae and class Poetea bulbosae including the Mediterranean plant groups of seasonal perennials and ephemera. The part of investigated plant groups are attributed to association Veronico dillenii-Secalietum sylvestris (Koelerion glaucae, order Festucetalia vaginatae) of the class Koelerio-Corynephoretea canescentis.
Keywords: heliophylous ephemeroids and winter ephemera plant groups, Braun-Blanquet method, Poetea bulbosae class, Koelerio-Corynephoretea canescentis class, Dnipro Forest-Steppe.